Application of mangifera indica (Mango) seed as a biosorbent for the removal of methyl red - Nur Hazirah Binti Mohd Yusoff (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
Mango seeds powder, has been investigate as an ideal alternative to be used in its natural form as a biosorbent for the removal of methyl red dye from its aqueous solutions. The effects of different system variables such as pH, adsorbent dosage, initial dye concentration, contact time and temperature were taken into account for the investigation and optimal experimental conditions were determined. The results showed that the optimum pH value for dye adsorption was 4.0. Optimum adsorbent dosage and initial dye concentration is found to be 0.05vg and 15.0 mg/50 ml with the percentage of removal is 43% and 68% respectively. Meanwhile, maximum dye was removed within 5 hours of the start of every experiment and favours temperature at 38C with the percentage of removal of 22% and 94% respectively. The Langmuir and Freundlich models were used for this study. It was found that the experimental results show that the Langmuir equation fit better than the Freundlich equation. The results indicate that the acidic pH supported the adsorption of the dye on the adsorbent. Furthermore, adsorption kinetics of the dye was studied and the rates of sorption were found to follow pseudo-second-order kinetics. Finally, the effect of adsorbent surface was analyzed and characterized by Field- Emission Scanning Electron Microscope (FE-SEM) and Fourier Transform Infrared Spectroscopy (FT-IR). The images of the results showed reasonable agreement with adsorption measurements.